RESPONSES TO COMPLIMENTS WITHIN MINANGKABAU FAMILIES IN PAUH, INDONESIA - angela flores (Salingka, 2019)
This study investigates the compliment responses used within Minangkabau nuclear families with low education levels in Pauh District, Indonesia from a pragmatic perspective. Responses to compliments on appearance and achievement addressed from one family member to another were classified according to Herbert's taxonomy. This model was modified to include two new categories of response. A simple “thank you” style response was rarely used. Relative status within a family was found to influence the preferred types of compliment response. This is a synchronic and descriptive study that used a qualitative approach. The data was gathered in the field using interviews and observation. The analysis showed that the majority of the participant responses were in the agreement category and were often comment acceptances such as of course! I’m handsome since I was born! etc. It appeared that the participants’ preferences were influenced by relative status and the Minangkabau predisposition for joking.